Parental and Children Language Politeness Strategies as a Form of Education in Family - Mayrita, Hastari; Balkist, Putri Sukma; Muchti, Andina; Ernawati, Yeni (Universitas Jambi, Indonesia, 2023)
The research aimed to explore the forms of language politeness principles for parents and young children in the family environment and to describe how parents instill politeness in early childhood in the family environment. A research method is a qualitative case study. Researchers used observation, note-taking, and recording techniques in data collection. Data Analysis was carried out chronologically and categorically. The findings of this research were six forms of politeness principles, namely the maxim of tact, generosity, acceptance, humility, agreement, and sympathy from various interactions. Based on the findings of politeness maxims, it is necessary to apply politeness patterns to children in the family. It is to foster children's language behavior under the expectations and upbringing of parents because language behavior in the family influences their language behavior.